Production of silica gel from rice husk - Binasoy, Reuben Benjamin Q.; Calagui, Almer U.; Ramos, Ramon Emilio R.; Suero, Michael Oliver B. (College of Engineering, 1998)
Product: White silica gel -- Capacity: 900,000 kilograms per year -- Selling price: Php 60.00 per kg -- Total capital investment: Php 85,514,463.00 -- Total product cost: Php 33,560,018.00 -- ROI: 19.88% -- Payback period: 4.41 years -- Plant location: First Bulacan Industrial City, Tical, Malolos, Bulacan